Results of Arthroscopic Treatment in Unresolved Osgood-Schlatter Disease in Athletes. Issue 2 (28th February 2017) - Circi, Esra; Beyzadeoglu, Tahsin
Purpose: Osgood-Schlatter disease (OSD) is common causes of knee pain in adolescent. Most patients respond to conservative treatment. However surgical treatment has been recommended for unresolved OSD. The aim of this study was to determine the outcomes of arthroscopic ossicle excision in athletes with unresolved OSD. Methods: Between September 2008 and November 2014, arthroscopy was performed 11 knees of 11 patients with OSD. The inclusion criteria were patients who underwent arthroscopic surgery with more than one year follow-up after surgery. Patients have a documented history of OSD with refractory pain over the tibial tubercle for a mean of 15.5 months (range, 7 to 24 months; SD, 7.5 months). The mean age was 23 years (range, 19 to 29 years; SD, 2.8 years). The mean follow-up period was 66.1 months (range, 15 to 96 months; SD, 25.6 months). Results: The mean return the sports activities after the surgery was 6.7 weeks (range 5 to 9 weeks; SD 1.3 weeks). The mean Kujala patellofemoral score improved from 82.9 (range 80 to 88 points; SD 2.6) preoperatively to 98.5 (range 96 to 100 points; SD 1.6) at final follow-up (p<0.01).In addition, the mean Lysholm knee scale was 87.5 (range 86 to 90 points; SD 1.7) in the preoperative period and increased to 96.9 (range 94 to 100 points; SD 2.5) at final follow-up(p<0.01). The mean Tegner activity level was 7.5 (range 6 to 8; SD 0.9) in the preoperative period and increased to 8.5 (range 7 to 9; SD 0.9) after surgery (p<0.01). Conclusions: We investigated the functional outcomes after arthroscopic treatment of unresolved OSD in athletes. In the all athletes, the arthroscopic treatment of OSD yielded satisfactory functional recovery. No postoperative complication were located. All patients were able to return the same level athletic activity. Level of evidence: Therapeutic Level IV. Key terms: Osgood-Schlatter disease, athletes, knee arthroscopy, ununited ossicle